1986
DOI: 10.3109/00365528609034622
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Hiatus Hernia to Reflux Oesophagitis A Prospective Study of Coincidence, Using Endoscopy

Abstract: A prospective study of the incidence of hiatus hernia and/or reflux oesophagitis was carried out in 670 patients referred for routine upper alimentary endoscopy. Hiatus hernia was found in 16.6% and reflux oesophagitis in 15.1% of the patients. Forty-two per cent of the patients with hernia did not have oesophagitis, whereas 63% of the patients with reflux oesophagitis had hernia. In patients without reflux oesophagitis the incidence of hiatus hernia was 8%. Reflux oesophagitis was significantly (p less than 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(66 citation statements)
references
References 6 publications
3
61
1
1
Order By: Relevance
“…Our own retro-spective series from Singapore showed that of 11943 patients undergoing diagnostic upper endoscopy for various complaints, 4% had esophagitis [19] . This frequency was lower than those reported from Western centers [20,21] . Thus, with the exception of the Taiwanese series, the proportion of patients with endoscopic esophagitis in Asian series appears lower than that in reports from Western countries.…”
Section: Prevalence Of Endoscopic Esophagitiscontrasting
confidence: 51%
See 2 more Smart Citations
“…Our own retro-spective series from Singapore showed that of 11943 patients undergoing diagnostic upper endoscopy for various complaints, 4% had esophagitis [19] . This frequency was lower than those reported from Western centers [20,21] . Thus, with the exception of the Taiwanese series, the proportion of patients with endoscopic esophagitis in Asian series appears lower than that in reports from Western countries.…”
Section: Prevalence Of Endoscopic Esophagitiscontrasting
confidence: 51%
“…In our retrospective series from Singapore, the proportion of hiatus hernia among patients seen for gastrointestinal complaints was 3% [19] . Thus, the available data show that the prevalence of hiatus hernia is lower than that in Western series (17%-22%) [20,21] .…”
Section: Prevalence Of Hiatus Herniamentioning
confidence: 89%
See 1 more Smart Citation
“…Today, the incidence of RE is reported to be 10%-20% in Europe and the United States [23][24][25] , and 14%-16% in Japan [26][27][28] . While the incidence of RE in Japan is considered low as compared to Europe and the United States, the incidence of RE in Japan has increased due to the westernization of the Japanese diet, the rapidly growing elderly population, and lower H pylori infection rates [26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…Another opinion was that the existence of HH did not affect esophageal sphincter competence [7][8][9][10] . The third opinion was that HH might play only a partial role in the development of esophagitis, that is, the absence of HH could exclude more severe forms of reflux esophagitis [11][12][13][14] . This study was, therefore, designed to evaluate the influence of the existence of HH on GER.…”
Section: Introductionmentioning
confidence: 99%